2015
DOI: 10.1111/jpn.12324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fish oil on the expression of genes involved in lipid metabolism in liver and skeletal muscle of lactating sows

Abstract: This study investigated the hypothesis that dietary supplementation of fish oil as a source of n-3 polyunsaturated fatty acids (PUFA) influences the expression of target genes of sterol regulatory element-binding proteins (SREBP)-1 and (SREBP)-2 involved in triacylglycerol (TAG) synthesis and fatty acid and cholesterol metabolism in the liver, and moreover activates the expression of target genes of peroxisome proliferation-activated receptor (PPAR)-α involved in TAG and fatty acid catabolism in liver and skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Tanghe et al (2013) reported that the perinatal sows' diet with sh oil had no effect on the oxidative stress state of sows [13]. However, the inconsistent reports found that dietary sh oil had no effect on the expression of genes related to cholesterol synthesis and absorption in the liver of lactation sows, but had minor effect on the hepatic lipid metabolism which had no effect on the milk production of sows [14]. Shen et al (2015) suggested that the supplementation of olive oil in the maternal diets signi cantly reduced IL-1β and TNF-α in the milk, but increased the oxidative stress of sows in sh oil group [15].…”
Section: Discussionmentioning
confidence: 99%
“…Tanghe et al (2013) reported that the perinatal sows' diet with sh oil had no effect on the oxidative stress state of sows [13]. However, the inconsistent reports found that dietary sh oil had no effect on the expression of genes related to cholesterol synthesis and absorption in the liver of lactation sows, but had minor effect on the hepatic lipid metabolism which had no effect on the milk production of sows [14]. Shen et al (2015) suggested that the supplementation of olive oil in the maternal diets signi cantly reduced IL-1β and TNF-α in the milk, but increased the oxidative stress of sows in sh oil group [15].…”
Section: Discussionmentioning
confidence: 99%
“…In experiment 2, twenty second parity sows (Large White and German Landrace) were used and artificially inseminated as described recently in more detail [ 35 ]. In brief, after farrowing the sows were randomly divided into two groups (control group and fish oil group) of 10 animals each, and litter sizes were adjusted to 8 piglets per sow and the sows of the two groups received two different diets throughout lactation.…”
Section: Methodsmentioning
confidence: 99%
“…In the control group, the diet contained 50 g of a mixture of palm oil and soybean oil (4:1, w/w, both oils were obtained from Henry Lamotte Oils GmbH, Bremen, Germany) per kg, whereas in the fish oil group the diet contained 50 g of fish oil (‘Marine oil’, obtained from Henry Lamotte Oils GmbH) per kg. A full description of the housing condition, diet composition, and feeding regime can be found in our recent publication [ 35 ]. In addition, data on daily feed intake, body weight development and energy balance of the sows have been reported there [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of primers used for qPCR analysis were as described recently (Rosenbaum et al 2013;Gessner et al 2015), except of primers for LDLR (for: 5ʹTGC GAA GAT ATC GAC GAG TG-3ʹ; rev: 5ʹTAC GGT CCA GGG TCA TCT TC-3ʹ). Characteristics of primers used for qPCR analysis were as described recently (Rosenbaum et al 2013;Gessner et al 2015), except of primers for LDLR (for: 5ʹTGC GAA GAT ATC GAC GAG TG-3ʹ; rev: 5ʹTAC GGT CCA GGG TCA TCT TC-3ʹ).…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%